أثر استخدام المحاكاة الحاسوبية في تنمية مهارة حل المسائل الفيزيائية لدى طلبة الصف الثاني الثانوي واتجاهاتهم نحو مادة الفيزياء = The effect of using computer simulation to develop physics problems solving skills for seconds class' students in secondary schools and their attitudes towards physics - Alsam, Abdullateef M.; Al-Hidabi, Dawood Abdulmalek Yahya; Alsham, Abdullah (the International Group for Consulting and Training (www.igctr.org) in collaboration with Jordanian Psychological Association, 2016)
The purpose of this study was to investigate the effect of using computer simulation to develop physics problems solving skills for second class’ students in secondary schools at Sana'a state and their attitudes towards Physics. To fulfill this goal, two scales were built; scale of physics problems solving skills, and scale of attitudes towards Physics. A program was designed by computer simulation to teach electricity and magnetism units. Then two groups were selected; the experimental group (41 students), and the control group (36 students). The application of tools and the analysis of the data have shown the following results: There were significant differences between the mean of the degrees of the experimental group and the control group in the physics problems solving skills scale in favor of the experimental group, There were significant differences in attitudes toward physics between the experimental group and the control group in favor of the experimental group, There were significant differences between the mean of the degrees of the experimental group and the control group in the physics problems solving skills scale related to students levels (over average - under average) in favor of the experimental group in over average and under average levels, And there were significant differences in attitudes toward physics between the experimental group and the control group related to students levels (over average - under average) in favor of the experimental group in over average and under average levels.